FINLAND AS A BUSINESS ENVIRONMENT FOR INTERNATIONAL E-COMMERCE - The role of transport service providers in enabling international small enterprise e-commerce - Niinimaa, Martti (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The growth of international e-commerce and it significance for the Finnish economy has been a subject of public discussion. In addition, e-commerce companies and their deliveries are a growing source of business for logistics and transport service providers. The purpose of this study was to gain better understanding of the Finnish business environment for international B2C e-commerce of small businesses and more specifically on the requirements it sets to the transport service providers serving these e-commerce businesses. The study used qualitative methods and a social constructive approach and collected the empirical data using interviews. The research can be described as abductive. Data was first collected with a sales personnel group interview within a logistics and transportation company, which assigned the research, to guide the research work. After that the main theoretical background work was conducted. The main data of the interview was collected from two case customers of the logistics and transport company. To enhance the data an interview of an e-commerce expert in a separate consulting company was also interviewed to gain better understanding of the phenomenon and the case customer data. The collected data was analyzed using thematic analysis. The main empirical findings of this study suggest the price of e-commerce related transportation is perceived as a major factor affecting the international sales of the case companies. Despite this various pricing models exists among e-commerce companies. The transport prices may act as temporary barrier for e-commerce growth, however, the expert interviews and data from large e-commerce enterprises suggest that this is rather related to the growth phase of the e-commerce companies, and not a persistent problem for e-commerce in Finland. The legislative environment in Finland was not seen to cause problems for Finnish e-commerce, although room for improvement was seen with regard to general business competitivity. The cognitive and normative environment, lack of examples of well know Finnish international e-commerce companies and perceived difficulty of international trade may, however, contribute to reluctance to internationalize. In addition, this has caused best practices for e-commerce not to have formed and adopted for Finnish e-commerce. The lack of large scale international e-commerce has also resulted in limited availability of expertise on such project, which may limit the further growth of Finnish e-commerce companies. More research would be needed on the pricing models of e-commerce deliveries, and the effects they have on online sales. In addition, more case research on successfully internationalized Finnish e-commerce companies is suggested.

Kansainvälisen verkkokaupan kasvu ja sen merkitys Suomen taloudelle on noussut yleiseksi puheenaiheeksi. Lisäksi verkkokaupat ja niiden tavaratoimitukset ovat kasvava liiketoiminnan lähde kuljetus- ja logistiikkayrityksille. Tämän tutkimuksen tarkoitus ymmärtää paremmin suomalaista liiketoimintaympäristöä pienten kansainvälistä kuluttajaverkkokauppaa harjoittavien yritysten kannalta verkkokauppojen näkökulmasta ja erityisesti sen asettamista vaatimuksista näitä yrityksiä palveleville logistiikka ja kuljetusyhtiöille. Tutkimus käytti kvalitatiivisia menetelmiä lähtökohtanaan sosiaalinen konstruktionismi ja empiirinen aineisto kerättiin haastattelujen avulla. Tutkimusta voi kuvailla myös abduktiiviseksi. Tietoa kerättiin ensin tutkimuksen toimeksiannon tehneen kuljetus- ja logistiikkayrityksen sisällä tutkimussuunnan ohjaamiseksi. Tämän jälkeen tehtiin tutkimuksen pääasiallinen teoreettinen taustatyö. Pääasiallinen empiirinen data kerättiin kahdelta case-asiakasyritykseltä. Tiedonkeruun vahvistamiseksi suoritettiin lopuksi verkkokauppa-asiantuntijan asiantuntijahaastattelu ulkopuolisessa konsulttiyrityksessä, jotta käsiteltäviä ilmiöitä ja case-asiakasdataa voitin paremmin ymmärtää. Päätutkimustuloksina kävi ilmi kuljetusten hinnoittelun uskottu merkittävä vaikutus verkkokauppojen kansainväliseen myyntiin. Tästä huolimatta verkkokauppojen kuljetushinnoittelumalleissa on yhä suuria eroja. Kuljetushinnat voivat aiheuttaa väliaikaisia esteitä verkkokauppojen kasvulle, mutta asiantuntijahaastattelun ja suurten kansainvälisten verkkokauppayritysten tietojen perusteella kuljetushinnat eivät ole ylitsepääsemätön este Suomalaisten verkkokauppojen kasvulle. Suomen lainsäädännöllinen toimintaympäristö ei aiheuta merkittäviä ongelmia erityisesti verkkokaupoille, joskin parantamisenvaraa nähtiin sen vaikutuksissa yritysten yleiseen kilpailukykyyn. Kognitiivinen ja normatiivinen toimintaympäristö, tunnettujen suomalaisten kansainvälistyneiden verkkokauppojen puute esimerkkeinä ja kansainvälisen kaupan koettu vaikeus saattavat aiheuttaa haluttomuutta kansainvälistyä. Lisäksi tästä on aiheutunut tilanne, jossa suomalaisia best-practice toimintamalleja ei ole syntynyt tai otettu käyttöön verkkokaupassa. Suurten kansainvälisten verkkokauppojen puute Suomessa on aiheuttanut myös tilanteen, jossa asiantuntemusta tämän tyyppisten projektien toteuttamiseen on hyvin rajoitetusti, mikä saattaa hidastaa verkkokauppojen kasvua myöhemmissä kehitysvaiheissa. Tutkimuksen perusteella ehdotetaan lisätutkimusta liittyen verkkokauppojen toimitusten hinnoittelumalleihin ja näiden vaikutukseen myyntiin.